2013
DOI: 10.20529/ijme.2013.008
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent, privacy and confidentiality practised by doctors of a tertiary care hospital in a developing country

Abstract: There has been a marked improvement as compared with the previous practices of biomedical ethics by the doctors of this public sector hospital. However, awareness sessions should be conducted to update / improve the knowledge of ethics among doctors to help them translate their knowledge into practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…In a study conducted in Northern India, only 38.4% of the doctors agreed on revealing a doctor's mistake to the patient. [3] Similar ndings were noted by Brogen et al [8] where doctors were generally not in favor of revealing doctors' mistakes to patients. In a case scenario-based question in our study, however, a higher percentage of doctors 66 (92%) would inform their colleagues regarding their error.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In a study conducted in Northern India, only 38.4% of the doctors agreed on revealing a doctor's mistake to the patient. [3] Similar ndings were noted by Brogen et al [8] where doctors were generally not in favor of revealing doctors' mistakes to patients. In a case scenario-based question in our study, however, a higher percentage of doctors 66 (92%) would inform their colleagues regarding their error.…”
Section: Discussionsupporting
confidence: 81%
“…A greater part of the doctors preferred to consult a colleague on an ethical problem (58%) compared to consulting heads of departments and supervisors. Studies conducted in Chennai, India [1] and in Manipur [3] revealed similar conclusions that the majority of the doctor's knowledge regarding clinical ethics was inadequate. Subramanian et al [1] similar to Hariharan et al [1] reported that the majority of the doctors remembered little of the Hippocratic Oath once taken.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…where informed consent was not taken from 33.6% of the patients and 56.9% of patients responded that they were not informed about the side effects of the prescribed medicines. 9 This strongly suggests that the practice of informed consent can be effectively established if the students are aware about the informed consent from the very beginning of their medical career.…”
Section: Table 1: Socio Demographic Informationmentioning
confidence: 99%
“…It needs to be introduced in education curricula, and training on clinical ethics in health care settings is also beneficial. 72,73 Medical schools organize clinico-pathological conferences (CPC) where students and faculty interact with each other, but discussions on judgments related to health care or liability cases and ethics are not often presented. Interactive programs in medical schools and clinical practices about such issues will help students and physicians understand not only the intricacies of laws related to health care and the shortcomings of health professionals and health systems, but also strengthen their understanding of ethics and laws, improve their practice and standard of care, and minimize litigation issues.…”
Section: Education and Trainingmentioning
confidence: 99%